Practical training manual on discipline "Metrology, standardization and conformity assessment" - Burova, М. Y.; Varavina, О. P.; Yatskevich, О. О. (My University, 2022)
The manual contains materials for practical lessons on discipline "Metrology, standardization and conformity assessment". The manual contains fundamental premises on measurement uniformity and processing, application of measurement results and conformity assessment procedures. Intended for students of the 5th course of specialty 185 "Oil and gas engineering and technology".
Keywords: practical training manual; non system units of physical quantities; calculation of convergence; measurement uncertainty assessment; presentation of essay